And after fire, the Cerrado flowers: A review of post-fire flowering in a tropical savanna - Fidelis, Alessandra [UNESP]; Zirondi, Heloiza L. [UNESP] (Elsevier, 2021)
Post-fire flowering is a fire-adaptive trait that is underused in fire ecology literature to describe plant responses to fire. Most of the species described so far as having this strategy occur in mediterranean vegetation, while less is known about this event in tropical savannas. European naturalists described this fire-related response in the Cerrado when visiting Brazil and the first experiments to show the stimulation of flowering by fire were carried out by L. Coutinho, a pioneer in fire and savanna ecology in Brazil. The present study reviewed the literature on the Cerrado and compiled a database with 402 species that had any flowering response related to fire. As a result, we classified species based on flowering responses to fire (fire-dependent, fire-stimulated, fire-independent and fire-sensitive). About 85% of all the species included in the database are known to flower after fire, most of which are eudicots of the families the Asteraceae and Fabaceae, and ca. 45% are forbs. According to the classification, 267 of the species are fire-stimulated, 73 are fire-dependent, while only 11 of all the species are fire-sensitive. We encourage the use of post-fire flowering response in the future to analyze plant community responses to fire and help address knowledge gaps about how fire affects plant community assembly in tropical savannas.
Keywords: Cerrado; Fire; Fire-adaptive trait; Flowering phenology; Post-fire flowering; Tropical savannas